De novo interstitial deletion of 11q14.3q22 in a boy with mild intellectual disability and short stature. Issue 4 (15th July 2022) - Kurt Colak, Fatma; Eyerci, Nilnur; Lafci, Naz Guleray
Abstract : Background: Interstitial deletions of the 11q region are infrequent. Nonrecurrent chromosomal rearrangements are observed with high variability in size and precise breakpoints of the deleted area. Moreover heterogeneous clinical findings are observed in those harboring 11q interstitial deletions. Main clinical features associated with these deletions include mild dysmorphic findings intellectual disability and moderate developmental or speech delay Method: Conventional high-resolution karyotyping along with microarray studies were performed for the index patient who was found to be a carrier of a de novo interstitial deletion in the long arm of chromosome 11 which is located between the 11q14 and 11q22 band regions. We also investigated the homologous chromosome with next-generation sequencing technology to search for unmasked recessive variants in genes on the nondeleted contralateral allele. Results: Cytogenetic analysis revealed a de novo interstitial deletion on the long arm of chromosome 11 46 XY del(11) (q14q22). Microarray analysis confirmed the deletion of 11.2 Mb in length mapping from 11q14.3 to 11q22.2 [arr (GRCh37) 11q14.3q22.1(90549863_101833022)x1 dn]. Whole-exome sequencing did not detect any other genetic variant (single nucleotide variant ) on the nondeleted allele. Conclusion: This study gave us the opportunity for an attempt to define the smallest region of overlap for frequently observed clinical findings by reviewing the literature.